Environmental reporting practices of Malaysian construction companies : a content analysis and perception study - Noor Afzalina Mohamad (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2012)
Pressure for companies to be accountable to a wider group of stakeholders has encouraged companies to provide additional information including social and environmental-related information. Accordingly, such information should be valuable in assisting stakeholders in their decision making. The present study examines the extent and quality of environmental reporting of the construction sector in Malaysia, and compares this information with the environmental information desired by potential customers. Quantitative content analysis and structured interviews were used to collect the data. A total of forty nine construction companies in Malaysia were examined and thirty potential customers were interviewed in the present study. The results reveal that while the extent of environmental disclosures was increasing, the quality of environmental disclosures is low. Additionally, the study found that there is a significant difference between environmental items as proposed by Clarkson et al. (2008) in their environmental disclosure index and environmental information actually reported by Malaysian construction companies. A significant difference further exists between environmental disclosure items actually disclosed by construction companies and the information desired by potential customers. The findings of the present study suggests that there is a need for detailed guidelines for environmental reporting to assist companies in providing environmental disclosures, to ensure that stakeholders' information needs are met. Additionally, the findings suggest that for environmentally-sensitive sectors such as the construction industry, there is a need for environmental reporting to be made mandatory. Further research examining the perceptions of other stakeholder groups, such as non-governmental organisations (NGOs) on environmental disclosures needed, is proposed.